Bridging the Gaps between Impact Assessments and Resettlement Planning: A Case Study of Padma Multipurpose Bridge Project, Bangladesh. (1st January 2016) - Mahmood, Muhammad Nateque; Keast, Robyn
Abstract: The traditional methodologies including spatial decision support systems have at times showed their ineffectiveness in terms of gathering, analyzing and incorporating diversified views of affected persons into resettlement planning. This ineffectiveness is in dealing with unstructured problems and uncertainty in analyzing alternative strategies. This paper therefore proposes an integrated methodology (combination of argumentative mapping and qualitative probabilistic networks) to counter these limitations. The new methodology was introduced in a large-scale infrastructure project to verify its applicability. Results derived from the study not only provide better insights into resettlement-related problems, but also indicate critical management options for desired objectives.